Cita Menuju Ideal Moral Al-Qur’an (Kajian atas Neo-Modernisme Fazlur Rahman) - Mudaris, Hudan (Al-Manahij: Jurnal Kajian Hukum Islam, 2009)
According to Fazlur Rahman, the interpretation of Qur’an verses should go along with the social changes. Meanwhile, still there is a phenomenon on arguing the best solution; maintaining the classical interpretation or building contextual ones. When changing happened there is a challenge to prove the existence of Qur’an.